Focus on 1,25-Dihydroxyvitamin D3 in the Peripheral Nervous System - Faye, Pierre Antoine; Poumeaud, François; Miressi, Federica; Lia, Anne Sophie; Demiot, Claire; Magy, Laurent; Favreau, Frédéric; Sturtz, Franck G. (Frontiers in Neuroscience, 2019)
In this review, we draw attention to the roles of calcitriol (1,25-dihydroxyvitamin D3) in the trophicity of the peripheral nervous system. Calcitriol has long been known to be crucial in phosphocalcium homeostasis. However, recent discoveries concerning its involvement in the immune system, anti-cancer defenses, and central nervous system development suggest a more pleiotropic role than previously thought. Several studies have highlighted the impact of calcitriol deficiency as a promoting factor of various central neurological diseases, such as multiple sclerosis, amyotrophic lateral sclerosis, Parkinson's disease, and Alzheimer's disease. Based on these findings and recent publications, a greater role for calcitriol may be envisioned in the peripheral nervous system. Indeed, calcitriol is involved in myelination, axonal homogeneity of peripheral nerves, and neuronal-cell differentiation. This may have useful clinical consequences, as calcitriol supplementation may be a simple means to avoid the onset and/or development of peripheral nervous-system disorders.